Magnetic Nanoparticles for the Delivery of Dapagliflozin to Hypoxic Tumors: Physicochemical Characterization and Cell Studies - Angelopoulou, Athina; Voulgari, Efstathia; Kolokithas-Ntoukas, Argiris; Bakandritsos, Aristides; Avgoustakis, Konstantinos (AAPS PharmSciTech, 2018)
In solid tumors, hypoxia (lack of oxygen) is developed, which leads to the development of resistance of tumor cells to chemotherapy and radiotherapy through various mechanisms. Nevertheless, hypoxic cells are particularly vulnerable when glycolysis is inhibited. For this reason, in this study, the development of magnetically targetable nanocarriers of the sodium-glucose transporter protein (SGLT2) inhibitor dapagliflozin (DAPA) was developed for the selective delivery of DAPA in tumors. This nanomedicine in combination with radiotherapy or chemotherapy should be useful for effective treatment of hypoxic tumors. The magnetic nanoparticles consisted of a magnetic iron oxide core and a poly(methacrylic acid)-graft-poly(ethyleneglycol methacrylate) (PMAA-g-PEGMA) polymeric shell. The drug (dapagliflozin) molecules were conjugated on the surface of these nanoparticles via in vivo hydrolysable ester bonds. The nanoparticles had an average size of ~ 70 nm and exhibited a DAPA loading capacity 10.75% (w/w) for a theoretical loading 21.68% (w/w). The magnetic responsiveness of the nanoparticles was confirmed with magnetophoresis experiments. The dapagliflozin-loaded magnetic nanoparticles exhibited excellent colloidal stability in aqueous and biological media. Minimal (less than 15% in 24 h) drug release from the nanoparticles occurred in physiological pH 7.4; however, drug release was significantly accelerated in pH 5.5. Drug release was also accelerated (triggered) under the influence of an alternating magnetic field. The DAPA-loaded nanoparticles exhibited higher in vitro anticancer activity (cytotoxicity) against A549 human lung cancer cells than free DAPA. The application of an external magnetic field gradient increased the uptake of nanoparticles by cells, leading to increased cytotoxicity. The results justify further in vivo studies of the suitability of DAPA-loaded magnetic nanoparticles for the treatment of hypoxic tumors.
Keywords: glukosidy; nanomedicína; Humans; Sodium-Glucose Transporter 2 Inhibitors; Benzhydryl Compounds; Drug Carriers; nádorová hypoxie; Nanomedicine; A549 Cells; Drug Delivery Systems; lidé; Drug Liberation; uvolňování léčiv; transportér 2 pro sodík a glukózu; Sodium-Glucose Transporter 2; lékové transportní systémy; glifloziny; nosiče léků; nádorové buněčné linie; Glucosides; magnetické nanočástice; Cell Line, Tumor; buňky A549; benzhydrylové sloučeniny; Magnetite Nanoparticles; Tumor Hypoxia